Surgical Management of Pseudophakic Malignant Glaucoma via Anterior Segment-Peripheral Iridectomy Capsulo-Hyaloidectomy and Anterior Vitrectomy - Basgil Pasaoglu, Isıl (Hindawi Publishing Corporation, 2012)
Purpose. To describe our surgical technique in the management of pseudophakic malignant glaucoma refractory to conventional treatment. Methods. Two pseudophakic eyes with malignant glaucoma underwent peripheral iridectomy, lens capsulectomy, hyaloidectomy, and anterior vitrectomy through a clear corneal incision by using a vitreous cutter. Results. Prompt resolution of malignant glaucoma was achieved in both cases and no recurrence was observed during postoperative followup of five months. Conclusions. An anterior segment surgeon can treat pseudophakic malignant glaucoma successfully by using a vitreous cutter inserted through a corneal incision and performing peripheral iridectomy, capsulo-hyaloidectomy, and anterior vitrectomy.